An experimental study on student credit cards in Singapore : how credit limits, privileges and money attitudes affect card application decisions and intended card usage - Abdul Hafidz Haji Omar (2011)
This study examines how credit limits and privileges impact college students’ intentions to apply for and intentions to use student credit cards in the local Singapore context. It also adds to the limited available literature on money attitudes influencing students’ preferences for the two product attributes of student credit card in question.